一种二自由度并联电液振动台的机构和运动学研究 - 段云龙; 韩保红; 马英忱; 齐京礼 (Jixie chuandong)
A new kind of two-DOF parallel electro-hydraulic shaking table is presented.The component and degrees of freedom are introduced.The kinematic analysis and the Jacobian matrix are given,and the principle of control system is preliminarily discussed.The theoretical basis is provided for road transportation simulation equipment.